2009
DOI: 10.1016/j.jvs.2009.02.221
|View full text |Cite
|
Sign up to set email alerts
|

Is Endovascular Repair of Mycotic Aortic Aneurysms a Durable Treatment Option?

Abstract: Surg 2009;xx:xx-xx.Objectives: To update our previous systematic review of outcomes following synchronous carotid endarterectomy (CEA) and off-pump coronary artery bypass grafting (OFF-CABG).Design: A systematic review of operative risks reported in published studies of synchronous CEA plus OFF-CABG procedures.Results: We identified 12 eligible studies, including data on 324 synchronous CEA plus OFF-CABG procedures. Operative mortality was 1.5% (95% confidence interval (CI): 0.3-2.8), the risk of death or ipsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 0 publications
0
40
1
2
Order By: Relevance
“…In these patients, Vallejo and others reported that a combination (hybrid) of in situ reconstruction and EVT might be necessary. 190,228,[241][242][243][244][245][246][247][248] Subsequent explantation of EVT devices is especially challenging in patients with hybrid procedures and might not be technically feasible. Vallejo and colleagues 190 recommended EVT or hybrid procedures only in selected patients and concluded that open in situ repair remains the surgical management of choice.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…In these patients, Vallejo and others reported that a combination (hybrid) of in situ reconstruction and EVT might be necessary. 190,228,[241][242][243][244][245][246][247][248] Subsequent explantation of EVT devices is especially challenging in patients with hybrid procedures and might not be technically feasible. Vallejo and colleagues 190 recommended EVT or hybrid procedures only in selected patients and concluded that open in situ repair remains the surgical management of choice.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…After initial placement of the EVT device, explantation of the device and open surgical resection of the aortic MA and reconstruction may be considered in patients who can tolerate an open procedure. 189,227,228,[241][242][243][244][245][246][247][248] There are insufficient data to recommend EVT as the procedure of choice for patients with aortic MA (Figure 8 …”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] The crucial question of durability therefore remains unanswered. The aim of this European multicenter collaboration was to study the durability of endovascular treatment of MAA, by assessing the late infectionrelated complications and long-term survival.…”
Section: Editorial See P 2129 Clinical Perspective On P 2142mentioning
confidence: 99%
“…Pagrindiniai ligos simptomai yra nespecifiniai -skausmas, bendras silpnumas, dėl to MA dažnai įtariama pavėluotai [12]. Patologijai įtarti labai padeda čiuopiama atsiradusi pulsuojanti masė (dažnai rankose arba kojose), tačiau kitų lokalizacijų MA diagnostikai ypač svarbūs vaizdiniai tyrimai.…”
Section: įVadasunclassified